Effectiveness of the Implementation of Fiscal Federalism at the Local Level (Social Inquiry: Journal of Social Science Research, 2023)
This study was carried out in the initial stage of the implementation of federalism which has adopted fiscal federalism. The current public   finance management system adheres to intergovernmental fiscal transfer. During the study, civil servant adjustment by the federal government was ongoing. This study examines effectiveness of the implementation of fiscal federalism at the local level. It further analyses local level’s own source revenue. Following the Constitution of Nepal (2015), Local Government Operations Act (2017) defined Metropolitan, Sub-Metropolitan, Municipality, and Rural Municipality as Local Levels as well as Local Governments. The qualitative method was adopted to accomplish the study for fulfilling the effectiveness of implementation of fiscal federalism. Available literature and data were analysed and interpreted with relevant themes. Besides, some quantitative data have been presented for analysing the own source revenue of the local levels. The study found it interesting that not only the federal, and province governments transfer the budget to the local government, but the local governments also collect and share the budget for province governments. It seems top down transfer and bottom up sharing. Besides some confusion, conflict, and mismanagement, the effectiveness of implementation of the fiscal federalism seems positive because local governments are the nearest and dearest for people. Moreover, the own source revenue collection practice and tendency show that it will increase in future.